Endovascular Occlusion of a Renal Arteriovenous Fistula with Renal Vein Aneurysm Formation for Rupture Prevention. (31st October 2019) - Rhee, Yae Hyun; Busch, Lucas; Sansone, Roberto; Ertas, Neslihan; Floros, Nikolaos; Schelzig, Hubert; Mulorz, Joscha; Wagenhäuser, Markus Udo
Abstract : Purpose . To report the effectiveness of left renal artery (LRA) occlusion using Amplatzer Vascular Plug (AVP) II as treatment for a high-flow renal arteriovenous fistula (RAVF) with multiple renal vein aneurysms (RVA) to prevent aneurysm rupture and cardiac decompensation. Case Report . A 59-year-old female suffering from a post-traumatic RAVF presented with tachycardia and increased cardiac output (CO). Doppler ultrasonography and computed tomography (CT) scan revealed a high-flow RAVF with multiple RVAs and unilateral critically reduced kidney function. Appreciating recent interventional therapeutic advances, the patient was treated with endovascular placement of AVP II into the left renal artery (LRA) resulting in complete occlusion of the RAVF to effectively reduce the risk of RVA rupture and cardiac decompensation. No anti-platelet medication was administrated after the occlusion of the LRA. The patient's physical capacity improved since right heart volume strain was normalized, and CO was reduced. Conclusion . Transbrachial AVP II occlusion of the LRA is effective to occlude high-flow RAVFs to prevent risk of life-threatening RVA rupture. Additional follow-up is warranted to verify long-term effectiveness of this approach.